Diagnóstico situacional do descarte de pilhas, baterias de celulares e automotivas em São Luís-MA - Santos, Edenilde Alves dos (2013)
The present scientific study discussed how to dispose batteries, cell phone and automotive batteries by managers of commercial establishments, as well as the perception of the consumer population of batteries and cell phone batteries in São Luís, Maranhão. We conducted an exploratory study with a quantitative approach. The research was carried out in retailing goods stores in general and mobile telephony establishments and at the exit of the shops when referred to the consumer population. To collect data, we used a form with questions regarding demographics, socioeconomic factors, and level of knowledge about the disposal of batteries, cell phone batteries and automotive that applied to managers and consumer population. Data collection occurred from February to August 2012. The project was submitted to the Ethics Committee of the Universidade Federal do Maranhão, obtaining assent under the protocol number 23115-017233/2011-11. The results showed that a large proportion of managers unknow the composition of the batteries that comercialize, as well as legislation and environmental problems and public health that such waste may cause to the environment and human health; managers never received training or course on disposal of batteries or inspection by the competent bodies, Establishments traded automotive batteries only had selective collection service for financial issue and referred these products at end of life for sorting units, while those who traded ordinary batteries and cell phone batteries mostly lacked collection service, claiming as reasons for not collecting missing information, monitoring, environmental education and for being an unnecessary service and the ones who had collected, gave final destination inappropriate as household waste .The majority of consumers interviewed used daily batteries and cell phones, unaware of the existence of collection points, as well as the composition of batteries, legislation and environmental issues and public health that such waste may cause to the environment and human health. Consumers interviewed mostly discarded improperly batteries and cell phones at the end of life.